Interação YAP1-TEAD regula a cascata de sinalização do EGF em células do cumulus em bovinos - Koch, Júlia (2020)
The mechanism of cumulus cell (CC) expansion and ovulation in vivo is triggered by LH surge in granulosa cells and CC, which culminating in a series of paracrine and autocrine communications between these ovarian cells. It is well established that granulosa-secreted factors act on CC, stimulating important genes involved in cumulus expansion, oocyte maturation and ovulation. Although several signaling pathways involved in this process are already known, there is no complete understanding in this physiological process. Recently, the Hippo signaling pathway and its effectors (YAP1 and TAZ) have been related to different contexts of ovarian physiology, including the ovulatory process, in mice and humans. However, few studies relating this pathway are available in economic relevant species. The aim of this study was to demonstrate the function of YAP1-TEAD interaction in the modulation of key genes for expansion and ovulatory mechanism, as well as, their regulation in bovine cumulus cells. For this, cumulus-oocyte complexes (COCs) were in vitro cultured during 0 or 12h and subjected to immunofluorescence to demonstrate YAP1 and pYAP1 intracellular localization. Our results suggest that YAP1 translocates from the cytoplasm to the nucleus during in vitro maturation (IVM) time. To elucidate YAP1 regulation, we inhibited EGF receptor (EGFR, with AG 1478) and stimulated COCs with EGF or FSH. Thus, EGFR inhibition results in reduction of YAP1 and CTGF (one of the major YAP1-TEAD target genes) expression. Then, COCs were subjected to different concentrations of verteporfin, an YAP1-TEAD inhibitor, and it was obtained dose-dependent reduction of cumulus expansion (HAS2 and PTX3) and ovulation (ADAM17, EREG and PTGS2) related genes. Based on that, it is suggested that YAP1-TEAD interaction is involved in the expression of key genes for cumulus expansion and ovulation in bovine cumulus cells. Also, YAP1 regulation is mediated through EGFR stimulation, by EGF direct action, or FSH indirect action.